Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=>x\left(\dfrac{1}{2}+\dfrac{2}{3}\right)=\dfrac{10}{3}+1=\dfrac{13}{3}\)
\(=>x=\dfrac{13}{3}:\left(\dfrac{1}{2}+\dfrac{2}{3}\right)=\dfrac{13}{3}:\dfrac{7}{6}=\dfrac{26}{7}\)
5/6x - 1 = 10/3
5/6x = 10/3 + 1 = 13/3
X = 13/3 : 5/6 = 26/5
\(\dfrac{-3}{2}\times\dfrac{-15}{64}+\left(0,8-2\dfrac{4}{5}\right):3\dfrac{2}{3}\\ =\dfrac{45}{128}+\left(-2\right)\times\dfrac{3}{11}\\ =\dfrac{45}{128}-\dfrac{6}{11}\\ =-\dfrac{273}{1408}\)
a: \(=\dfrac{\left(1.6-1.6\right)\cdot\left(2.29-0.76\right)}{1.6+2.53}\cdot\dfrac{3.06:7.5+3.4\cdot0.38}{19-2.6\cdot0.5}=0\)
b: \(=\dfrac{17.8\cdot9.4-7.8\cdot9}{3-0.3\cdot0.3}=\dfrac{97.12}{2.4}=\dfrac{607}{15}\)
\(\frac{0,4\cdot13,68\cdot0,9 +0,6\cdot48,24\cdot0,6+0,2\cdot38,08\cdot1,8}{5:0,125+8:0,25}\)
Tử số : 0,4 x 13,68 x 0,9 +0,6 x 48,24 x 0,6 + 0,2 x 38,08 x 1,8
= 0,36 x 13,68 + 0,36 x 48,24 + 0,36 x 38,08
= 0,36 x ( 13,68 + 48,24 + 38,08 )
= 0,36 x 100
= 36
Mẫu số : 5 : 0,125 + 8 : 0,25
= 5 x 8 + 8 x 4
= 8 x ( 5 + 4 )
= 8 x 9
= 27
Vậy : \(\frac{0,4\cdot13,38\cdot0,9+0,6\cdot48,24\cdot0,6+0,2\cdot38,08\cdot1,8}{5:0,125+8:0,25}=\frac{36}{27}=\frac{4}{3}\)
a) \(0,25-\dfrac{2}{3}+1\dfrac{1}{4}\)
\(=\dfrac{1}{4}-\dfrac{2}{3}+\dfrac{5}{4}\)
\(=\dfrac{3}{12}-\dfrac{8}{12}+\dfrac{15}{12}\)
\(=\dfrac{10}{12}\)
\(=\dfrac{5}{6}\)
\(---\)
b) \(\dfrac{3^2}{2}:\dfrac{1}{4}+\dfrac{3}{4}\cdot2010\)
\(=\dfrac{9}{2}\cdot4+\dfrac{3015}{2}\)
\(=18+\dfrac{3015}{2}\)
\(=\dfrac{36}{2}+\dfrac{3015}{2}\)
\(=\dfrac{3051}{2}\)
\(---\)
c) \(\left\{\left[\left(\dfrac{1}{25}-0,6\right)^2:\dfrac{49}{125}\right]\cdot\dfrac{5}{6}\right\}-\left[\left(\dfrac{-1}{3}\right)+\dfrac{1}{2}\right]\)
\(=\left\{\left[\left(-\dfrac{14}{25}\right)^2:\dfrac{49}{125}\right]\cdot\dfrac{5}{6}\right\}-\left[\left(\dfrac{-2}{6}\right)+\dfrac{3}{6}\right]\)
\(=\left\{\left[\dfrac{196}{625}\cdot\dfrac{125}{49}\right]\cdot\dfrac{5}{6}\right\}-\dfrac{1}{6}\)
\(=\left\{\dfrac{4}{5}\cdot\dfrac{5}{6}\right\}-\dfrac{1}{6}\)
\(=\dfrac{4}{6}-\dfrac{1}{6}\)
\(=\dfrac{3}{6}\)
\(=\dfrac{1}{2}\)
\(---\)
d) \(\left(-\dfrac{1}{2}-\dfrac{1}{3}\right)^2:\left[\left(\dfrac{-5}{36}\right)-\left(\dfrac{-5}{36}\right)^0\right]\)
\(=\left(-\dfrac{3}{6}-\dfrac{2}{6}\right)^2:\left[-\dfrac{5}{36}-1\right]\)
\(=\left(-\dfrac{5}{6}\right)^2:\left[-\dfrac{5}{36}-\dfrac{36}{36}\right]\)
\(=\dfrac{25}{36}:\left(\dfrac{-41}{36}\right)\)
\(=\dfrac{25}{36}\cdot\left(\dfrac{-36}{41}\right)\)
\(=-\dfrac{25}{41}\)
#\(Toru\)